Arbejdsprøve med Roesaamaskiner og Radrensere paa Rosenfeldt ved Vordingborg i 1907. - Birk, C. V. (Tidsskrift for Landøkonomi, 2018)
Arbejdsprøve med Roesaamaskiner og Radrensere paa Rosenfeldt ved Vordingborg i 1907.